Adapting "the Epic of Nalandangan Matabagka Searches for the Deity of the Wind" into a children's storybook to convey a record of the culture and values found in Talaandig oral literature to grade school students ages 9 to 11 - Dancel, Waywaya E.; Aguilar-Reyes, Mitzi Marie (Quezon City College of Fine Arts, University of the Philippines Diliman, 2018)
Talaandig oral literature serves as a reminder for the community to uphold its values and to preserve the traditions of their pre-colonial ancestors. The Talaandig have resisted the effects of colonialism by teaching their predecessors the native ways. They established the School of Living Traditions, a learning center where they teach indigenous education to remind themselves of their culture back when there were no foreign invaders. Successfully, by going back to the roots of their identity they have advanced forward as a community. The problem of Filipino children who reside in urban areas is they don't have much as much access to oral literature like the Talaandig's Ulaging epic. The Ulaging is the story of the legendary figures like Matabagka and Agyo. An epic is a long poem that is rich in the morals and teachings. Many of their teachings seem like simple philosophy because common sense grounds the framework of their mentality. Through an excerpt of the Ulaging chant, "The epic of Nalandangan: Matabagka Searches for the Deity f the Wild", this thesis proposes adapting the narrative of Matabagka into a children's storybook that will be distributed among students living in urban areas ages 9 to 11 in grades 4,5 and 6.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography : leaves 177-180.
Keywords: Nalandangan -- Epic -- Philippines; Philippine literature